The relationship between afterlife beliefs and mental wellbeing among Jordanian Muslim youth - Al-Issa, Riyad Salim; Krauss, Steven Eric; Roslan, Samsilah; Abdullah, Haslinda (Michigan Publishing, 2021)
Despite the centrality of beliefs in afterlife reward and punishment in the religious life of Muslims, few empirical studies have sought to understand how such beliefs affect the psychological state and social behavior of Muslims. Past related studies have concluded that these beliefs are unhealthy because they are positively associated with general anxiety and death anxiety. This finding contradicts a central notion in Islamic theology, which states that avoiding afterlife punishment and obtaining afterlife reward is the primary motive for Muslim religiosity. The current study attempts to deepen our understanding of how Islamic afterlife reward and punishment beliefs affect the psychological state of Muslims. The study suggests that the influence of Islamic afterlife beliefs on wellbeing can be better understood from the perspective of meaning management theory as well as through the eudaimonistic tradition. This study has two goals: To develop the Islamic Afterlife Reward and Punishment Beliefs (IARPB) scale and to examine the relationship between IARPB and Muslim religiosity, death anxiety, death acceptance, and integrity. Data were collected from Jordanian university students (N = 605). Exploratory and confirmatory analyses support the construct validity of the IARPB Scale. IARPB positively predicted Muslim religiosity, death anxiety, death acceptance, and integrity. Results of ad hoc analysis indicated that IARPB suppresses death anxiety and amplifies death acceptance by increasing Muslim religiosity. In general, the results indicate a positive relationship between IARPB and the psychological state of Muslims. The limitations of the study and suggestions for future research are discussed.